PELAYANAN PUBLIK DAN OMBUDSMAN - Syof yan; Mis ri; Edi Sofian; Us man (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
This paper talks about the role of Ombudsman in order to realize clean government and good governance especially for government agencies Clean Goernment and Good Governance in relation to good governance in the form of Public services to the public include aspects; The judicial system (the supremacy of law) and the government responsible for running the public service efficiently. In supporting the ability of a government in implementing Good Governance, there are three key pillars in its alignment: Government (the state), civil society (Society of Adab, civil society, civil society), and the market or the world Business. The three pillars are the parties that are integrated in the realization of Good Governance. In the context of institutional or institutional, the two pillars of Clean Governance mentioned above are the government, the business world (private), and the community in Public services must have a high synergy in the public service process. The third relationship can be explained by looking at the principal agent concept where the government is the agent who obtains the mandate of the community through the law to conduct public services to the business world and society as Principals who are then based on legislation involving other parties as a controlling the relationship is Ombudsma. Analysis uses the concept of 4 levels of economic institutional. The results of the analysis recommend: Good and Clean Governance is a reform demands that one form is improvement of public service. Referring to the law No. 25 on public services, the parties involved in the public service process are government agencies as agents, communities as principals and ombudsmen as third parties acting as supervisors and Mediator. The relationship between the government and the community can be explained by the concept of the principal agent that raises the problem of agency and problems arising between the two is resolved through the Ombudsman. The purpose of public service is to provide optimal preference for the community in fulfilling its needs by first fulfilling the requirements needed to obtain service. The Ombudsman as the agency being persuaded by the law should be able to minimize the costs arising from the public service process.